Retrospective Analysis of the Effect of Lidocaine Combined with Methylprednisolone on Pain Control After Uterine Artery Embolization - Yi Tang (Frontiers in Surgery, 2022)
BackgroundThe analgesic effect produced by the intra-arterial injection of lidocaine in patients undergoing uterine artery embolization has been proven to be safe and effective. Nevertheless, a significant degree of pain is typically experienced after the operation, and pain management is crucial. Methylprednisolone, which provides an anti-inflammatory effect, is widely used in the treatment of several diseases. To date, methylprednisolone has not been used after uterine artery embolization.MethodsA total of 131 patients with uterine leiomyoma were retrospectively enrolled. Forty-five patients (control group) were treated with embolized microspheres for bilateral uterine artery embolization. Fifty (study group) and 36 (lidocaine group) patients were administered lidocaine mixed with embolized microspheres during embolization, and in addition, the study group was administered methylprednisolone. Completed pain scales at different time points during surgery were obtained from patients undergoing uterine artery embolization. Efficacy against pain was evaluated by comparing the pain score, inflammatory index, and use of sufentanil within 24 h followed by a Kruskal-Wallis Test and a least significant difference post-hoc analysis.ResultsThe postoperative pain scores at 1, 4, and 7 h after uterine artery embolization in the study group (3.08 ± 2.09, 2.46 ± 1.93, and 2.38 ± 1.85, respectively) were significantly lower than those in the control group (4.84 ± 2.36, 4.16 ± 1.87, and 3.56 ± 1.93, respectively) and the lidocaine group (3.50 ± 2.10, 3.30 ± 1.88, and 3.28 ± 1.89, respectively). At the first 24 h after embolization, the total usage of sufentanil in the study group (31.4 ± 4.16) was significantly lower than those in the control group (45.7 ± 6.51) and the lidocaine group (38.3 ± 6.25). At 1 and 4 h, the pain scores of the lidocaine group were significantly lower than those of the control group. In addition, at the first 24 h after embolization, the total usage of sufentanil in the lidocaine group was significantly lower than that in the control group.ConclusionLidocaine in combination with methylprednisolone can significantly alleviate pain and reduce the usage of sufentanil after bilateral uterine artery embolization. Thus, methylprednisolone is a recommended addition to the therapeutic regimen after embolization.